2017
DOI: 10.1007/s12529-017-9643-6
|View full text |Cite
|
Sign up to set email alerts
|

Self-management and Shared Decision-Making in Alcohol Dependence via a Mobile App: a Pilot Study

Abstract: SIDEAL is a well-accepted and highly used app by AD patients that could improve their efficacy in managing their AD. Further larger, randomized studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 22 publications
1
50
0
2
Order By: Relevance
“…The former tools are usually preferred for their simplicity, but in the last few years a relevant number of Apps (e.g. Drinkaware) have been developed for this monitoring purpose, 33 making prospective measurement of drinking much easier for motivated patients. A good alternative to quantity frequency questionnaires is the use of screening instruments.…”
Section: Alcohol Use Disordersmentioning
confidence: 99%
“…The former tools are usually preferred for their simplicity, but in the last few years a relevant number of Apps (e.g. Drinkaware) have been developed for this monitoring purpose, 33 making prospective measurement of drinking much easier for motivated patients. A good alternative to quantity frequency questionnaires is the use of screening instruments.…”
Section: Alcohol Use Disordersmentioning
confidence: 99%
“…There is extensive empirical evidence for self-management strategies for a range of chronic health issues [ 22 ]. Some preliminary research suggests that self-management interventions may be useful for treating addictions to alcohol [ 28 30 ] and cannabis [ 31 ]. A review found that self-administered treatments (e.g., self-help book) are effective for treating mild alcohol abuse while more severe cases show better outcomes with the use of therapist mediated treatments [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining four articles directly or indirectly involved a human guide or clinician in some way: Urbanoski et al explored the role of health education moderators in an online community for 205 users of a self-help program for reducing problematic alcohol use [7]; Barrio et al evaluated feasibility and satisfaction with an app for self-registration of alcohol consumption and medication adherence among 24 outpatients with alcohol use disorder [9]; Kay-Lambkin et al found that alliance factors such as client initiative, perfectionism, and need for approval differentially moderated outcome for 274 participants with comorbid depression and alcohol/cannabis use, randomized to therapist-delivered CBT, supportive counseling, or computer-delivered therapy with brief therapist assistance [10]; and Bjelland et al explored qualitative aspects of alliance following use of a self-help film in the early stages of addiction treatment among 12 patients and 22 therapists [11]. Three of the studies included small samples [6,9,11], while the other three analyzed larger samples, requiring quantitative analyses to complement the qualitative interpretation [7,8,10].…”
Section: Engaging Users and Establishing A Working Alliancementioning
confidence: 99%
“…The same held for the text message study, where the researchers invested highly in adapting the intervention to suit the habits and needs of socially disadvantaged men, succeeding in eliciting responses to most of the messages, frequently including sensitive personal information, and responding as intended to behavior change components in text messages [8]. Similarly, the Barrio et al study suggested that regular monitoring and feedback in an attractive app package, as a complement to outpatient care, were perceived by participants as useful and helpful for achieving drinking goals (primarily controlled drinking) [9]. What these studies had in common was a high level of adaptation and attunement to user needs which, if perceived as expressions of empathy by the users, could constitute factors that have been demonstrated to be effective in psychotherapeutic processes [17].…”
Section: Engaging Users and Establishing A Working Alliancementioning
confidence: 99%
See 1 more Smart Citation